The 1257 CE cataclysmic eruption of Samalas volcano (Indonesia) revealed by indigenous written sources: Forgotten kingdoms, emergency response, and societal recovery - Malawani, Mukhamad Ngainul (Elsevier B.V., 2022)
Historical and archaeological findings have revealed that many human civilizations have been strongly affected by natural hazards, such as volcanic eruptions. An issue that still lacks attention is the response of ancient populations following eruptions as well as their resilience strategies. Three written sources from Lombok, Indonesia, provide descriptions of the ancient landscape of Lombok and the population's response to the Samalas volcano eruption in 1257 CE. The sources depict the conditions of Lombok and the surrounding areas during the pre-, onset-, and post-eruption phases of a catastrophic volcanic eruption with a volcanic explosivity index 7. Various responses of the inhabitants to the eruption are described in the sources, such as fleeing to the hills, avoiding hazards, and escaping to neighboring villages or islands. Several geographic features and toponyms are mentioned, allowing us to reconstruct the evacuation process during the crisis period. The sources also describe recovery strategies in the post-eruption period, including governance strategies, the rebuilding of cities and villages, and agriculture. The historical record suggests that Lombok may have taken up to a century to recover from the eruption and that new kingdoms and principalities became established by the fourteenth century. Disaster management related to the eruption is described in the texts from Lombok, but not in older written sources from Indonesia. © 2022 Elsevier B.V.